1978
DOI: 10.1111/j.1095-8649.1978.tb03480.x
|View full text |Cite
|
Sign up to set email alerts
|

The hearing of the Atlantic Salmon, Salmo salar

Abstract: The hearing of the salmon, Sulmo sular L., was studied by means of a cardiac conditioning technique. Fish were trained to show a slowing of the heart, on hearing a sound, in anticipation of a mild electric shock applied later. The minimum sound level to which the fish would respond was determined for a range of pure tones, both in the sea, and in the laboratory. The fish responded only to low frequency tones (below 380 Hz), and particle motion, rather than sound pressure, proved to be the relevant stimulus. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
122
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(125 citation statements)
references
References 23 publications
2
122
0
1
Order By: Relevance
“…Salmonids are considered hearing "generalists" and can detect sounds up to 500 or 600 Hz. We exposed salmonid fry to pure tone frequencies of 150, 180, and 200 Hz, which are well within the published hearing range of salmonids (Hawkins and Johnstone 1978).…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…Salmonids are considered hearing "generalists" and can detect sounds up to 500 or 600 Hz. We exposed salmonid fry to pure tone frequencies of 150, 180, and 200 Hz, which are well within the published hearing range of salmonids (Hawkins and Johnstone 1978).…”
mentioning
confidence: 64%
“…Studies have shown that the upper-threshold hearing range for salmonids is 380 Hz, with the scale rising steeply above 200 Hz (Knudsen et al 1992). Other researchers demonstrated that high frequency (150 Hz) at high intensity (4 m/s 2 ) did not cause any change in behavior (Hawkins andJohnstone 1978, Knudsen et al 1994). Other studies (notably Loeffleman et al 1991a,b) have reported success in diverting steelhead and chinook salmon smolts using variable frequencies from 60 to 120 Hz in a pulsed pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Thus field studies show that cods are substantially affected by altered ambient noise in their natural environment (Chapman and Hawkins 1973;Hawkins and Chapman 1975), whereas Atlantic salmon Salmo salar were only masked by sea noise at levels substantially above the ambient levels in one of its habitats (a Scottish loch; Hawkins and Johnstone 1978). The present study has demonstrated that sunfish are substantially less affected by the same amount of background noise (because of their lower hearing sensitivity) than two otophysines, although there is only a small difference in the T/N ratio of these three species.…”
Section: Differential Effects Of Background Noise On Hearing Sensitivitymentioning
confidence: 99%
“…Sounds from different sources provide them with information relevant for survival, e.g., finding mates and prey or avoiding predators. The natural environment of fishes, especially that of marine fishes (Knudsen et al 1948;Wenz 1962;Urick 1983;Myrberg 1990), but also freshwater habitats (Hawkins and Johnstone 1978;Rogers and Cox 1988;Lugli and Fine 2003), is characterized by a permanent background noise of abiotic (currents, rain, seismic events, coastal surf) and biotic (vocalizations of animals, photosynthesis) origin. In addition, the amount of man-made noise caused by ship and air traffic, hydroelectric power plants, or drilling is increasing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation